2012
DOI: 10.1134/s0036024412030314
|View full text |Cite
|
Sign up to set email alerts
|

The thermodynamic characteristics of the formation of Al3+ ion complexes with iminodisuccinic acid in aqueous solutions

Abstract: Complex formation between Al 3+ and iminodisuccinic acid (H 4 L) was studied at 25°C against the background of 0.1, 0.4, 0.6, and 0.8 N solutions of KNO 3 by potentiometry and mathematical modeling. The extrapolation of concentration constants to zero ionic strength was used to calculate the thermodynamic con stants of the formation of the AlL -, AlHL, and AlOHL 2-complexes using an equation with one individual parameter (logβ 0 = 16.48 ± 0.08, 8.93 ± 0.14, and 22.88 ± 0.08, respectively).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
1
0
2
Order By: Relevance
“…Так установлено, что иминодиуксусная кислота (ИДУК) проявляет весьма низкую токсичность для рыб, дафний и водорослей [10]. Для замены классических комплексонов, загрязняющих окружающую среду, тверскими учеными классического университета и сельскохозяйственной академии синтезированы и апробированы экологически безопасные комплексоны, производные дикарбоновых кислот [11][12][13][14][15].…”
Section: изменение гликолитической активности дрожжевых микроорганизм...unclassified
“…Так установлено, что иминодиуксусная кислота (ИДУК) проявляет весьма низкую токсичность для рыб, дафний и водорослей [10]. Для замены классических комплексонов, загрязняющих окружающую среду, тверскими учеными классического университета и сельскохозяйственной академии синтезированы и апробированы экологически безопасные комплексоны, производные дикарбоновых кислот [11][12][13][14][15].…”
Section: изменение гликолитической активности дрожжевых микроорганизм...unclassified
“…В указанных обстоятельствах предпочтительными являются комплексоны, способные к быстрому разложению в условиях окружающей среды и поэтому не загрязняющие природу. Такими свойствами обладают комплексоны, производные янтарной кислоты, физико-химические свойства которых изучаются около полувека [2][3][4][5]. Установлено, что они предпочтительны для использования в качестве транспортного средства при доставке биологически активных ионов металлов, а также различных генных конструкций в клетки живого организма [6].…”
Section: ключевые словаunclassified
“…The findings revealed that EDTA and other chelators exhibited effective adsorption of toxic cooking oil, including Pb and As, in soil 5 . Tolkacheva et al conducted research demonstrating that the chelating agent IDS can form stable complexes through its reaction with Al 3+ 6 . Furthermore, Xu et al discovered that the anion present in the chelating agent IDS can react with easily precipitated ions in coal, such as Ca 2+ and Mg 2+ forming stable cyclic complexes.…”
Section: Introductionmentioning
confidence: 99%